(untitled) (Journal of Economic Research & Business Administration, 2022)
In this research, an economic assessment of the role and results of small business activities in the Republic of Kazakhstan was carried out. The use of mathematically based methods to identify the main reasons for the decline in the performance indicators of small businesses during the pandemic is one of the most relevant areas of macroeconomic analysis, which ensures a higher quality of information about the development of the national economy. The purpose of this study is to use the methods of economic analysis to conduct a comprehensive assessment of the results of small businesses in Kazakhstan and assess the degree of its sustainability in crisis periods by comparing previously achieved indicators with those during the first half of the pandemic, as well as to assess how small business develops in Kazakhstan: by increasing resources or by increasing the return on use resource units. The paper used traditional methods of economic analysis, such as comparison and detailing, and traditional and deterministic methods of factor analysis. The secondary data of the «Taldau» information and analytical system of the Bureau of National Statistics of the Agency for Strategic Planning and Reforms of the Republic of Kazakhstan served as data sources. The study of trends in the development of small businesses in Kazakhstan revealed that during the pandemic, the proportion of the number of small entities from the total number of active entities in the economy, as well as the share of those employed in it, did not decrease; but in general, its development occurs mainly by increasing resources, rather than increasing the return on a unit of resource. The pandemic has been a difficult test for small businesses, but it has served as a source for strengthening them and increasing their resilience. Keywords: small business, national economy, unemployment rate, fixed assets, working capital, profitability indicators, financial stability.